Research on writing approaches in mental health - L'Abate, Luciano, 1928-; Sweeney, Laura G. (Bingley, U.K. : Emerald, 2011)
Writing as a medium of professional help and healing in the various interventional tiers of self-help, education, promotion, prevention, and psychotherapy, and rehabilitation has expanded exponentially since the introduction of computers and the Internet in the last generation. This volume does three things. Firstly, it brings together research on different types of writing and distance writing that have been, or need to be, used by mental health professionals. Secondly, it critically evaluates the therapeutic effectiveness of these writing practices, such as automatic writing, programmed writing poetry therapy, diaries, expressive writing and more. And thirdly, in addition to evaluating the effectiveness of various writing practices, the volume will examine how research-based writing approaches will influence the delivery of mental health services now and in the future, including the implications of these approaches.
ch. 1. The role of writing in mental health research / Laura G. Sweeney, Luciano L'Abate -- ch. 2. Writing in physical and concomitant mental illness : biological underpinnings and applications for practice / Brenda Stockdale -- ch. 3. Autobiographies / Lawrence Ressler, Luciano L'Abate -- ch. 4. Diaries / Thomas Mackrill -- ch. 5. Bibliotherapy / Debbie McCulliss -- ch. 6. The expressive writing method / Jenna L. Baddeley, James W. Pennebaker -- ch. 7. Poetry therapy / Debbie McCulliss -- ch. 8. Programmed writing / Luciano L'Abate -- ch. 9. Automatic writing / Laura G. Sweeney -- ch. 10. Epilogue : distance writing as the preferred medium of help and healing in the 21st century / Luciano L'Abate, Laura G. Sweeney.
Includes bibliographical references and index.
Keywords: Language Arts & Disciplines -- Communication Studies; Language Arts & Disciplines -- Authorship; Technical writing; Writing & editing guides; Writing skills; Creative writing -- Therapeutic use; Psychiatry -- Research